A companion to Gregory of Tours
1 online resource.
Keywords: Gregory, bishop of Tours (573-594), was among the most prolific writers of his age and uniquely managed to cover the genres of history, hagiography, and ecclesiastical instruction. He not only wrote about events (of the secular, spiritual, and even natural variety) but about himself as an actor and witness. Though his work (especially the Histories ) has been recycled and studied for centuries, our grasp of an even basic understanding of it, never mind Gregory’s significance in the history of the late antique West, has hardly yet attained a definitive perspective. A Companion to Gregory of Tours brings together fourteen scholars who provide an expert guide to interpreting his works, his period, and his legacy in religious and historical studies. Contributors are: Pascale Bourgain, Roger Collins, John J. Contreni, Stefan Esders, Martin Heinzelmann, Yitzhak Hen, John K. Kitchen, Simon Loseby, Alexander Callander Murray, Patrick Périn, Joachim Pizarro, Helmut Reimitz, Michael Roberts, Richard Shaw.